Hepatitis E virus infection as a direct cause of neuralgic amyotrophy. Issue 2 (28th June 2016) - Silva, Mauro; Wicki, Benoît; Tsouni, Pinelopi; Cunningham, Sophie; Doerig, Christopher; Zanetti, Giorgio; Aubert, Vincent; Sahli, Roland; Moradpour, Darius; Kuntzer, Thierry
ABSTRACT: Introduction : We describe a patient who developed neuralgic amyotrophy (NA) related to hepatitis E virus (HEV) infection. Methods : The patient underwent neurological and electrodiagnostic examinations, high‐resolution analysis of serological changes, and HEV load profile, and was treated with intravenous immunoglobulin. Results : There was evidence of bilateral, asymmetric acute inflammatory cervical polyradiculopathy and possible brachial plexopathy. Positive serum anti‐HEV IgM was followed by seroconversion to anti‐HEV IgG positivity. A calculated anti‐HEV antibody index was compatible with intrathecal synthesis, and HEV genotype 3 RNA was found in serum and cerebrospinal fluid (CSF). Liver function tests returned to normal within 6 weeks. Conclusions : Bilateral involvement of cervical nerve roots and/or plexus, elevated liver function tests, and abnormal CSF are typical features of HEV‐associated NA. The pathogenesis involves possible immune‐mediated mechanisms. However, our findings support the hypothesis that HEV‐related NA is associated with direct infection. Muscle Nerve 54 : 325–327, 2016